MANAJEMEN PENDIDIKAN ISLAM MODERN DI PONDOK PESANTREN AL MA’HAD AL ISLAMY ERA SOCIETY 5.0 (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
This research aims to analyze the modernization of Islamic education management at the Al Ma'had Al Islamy Al Ma'ruf Kudus Islamic Boarding School in facing the challenges of the Society 5.0 era. The research uses qualitative methods based on field studies and literature, with data collection techniques in the form of observation, interviews and documentation. The main focus of research includes curriculum updates, digital infrastructure development, increasing human resource competencies, as well as collaboration with industry and other educational institutions. The research results show that Islamic boarding schools have integrated technology in various aspects of management, such as administration, communication and learning, with an approach based on Islamic values. The innovations carried out include providing fast internet access, computer laboratories and digital literacy training programs for staff and students. In addition, the Islamic boarding school curriculum was updated to include relevant subjects, such as entrepreneurship and information technology. This strategy allows Islamic boarding schools to increase operational efficiency, educational relevance and competitiveness in facing changes in the Society 5.0 era. This research contributes to the development of an Islamic boarding school management model that integrates tradition with modern technology-based management practices, ensuring that Islamic boarding schools remain relevant and competitive amidst global dynamics.